Bronchoscopy in children with COVID‐19: A case series. Issue 10 (13th August 2020) - Goussard, Pierre; Van Wyk, Lizelle; Burke, Jonathan; Malherbe, Annemie; Retief, Francois; Andronikou, Savvas; Mfingwana, Lunga; Ruttens, Dries; Van der Zalm, Marieke; Dramowski, Angela; Da Costa, Aishah; Rabie, Helena
Abstract: Introduction: The coronavirus disease‐2019 (COVID‐19) era is a challenging time for respiratory teams to protect their patients and staff. COVID‐19 is predominantly transmitted by respiratory droplets; in the clinical setting, aerosol generating procedures pose the greatest risk for COVID‐19 transmission. Bronchoscopy is associated with increased risk of patient‐to‐health care worker transmission, owing to aerosolized viral particles which may be inhaled and also result in environmental contamination of surfaces. Methods: We describe our experience with the use of modified full‐face snorkeling masks for pediatric bronchoscopy procedures in four COVID‐19 infected children when filtering facepieces/respirators were in limited supply. Results: Bronchoscopy was urgently required in four children, and could not be delayed until COVID‐19 test results were available. During the pandemic peak, when respirators were in short supply, modified full‐face snorkel masks (SEAC Libera, SEAC, Italy) were worn by the bronchoscopy team. Each mask was fitted with an O‐ring, adapter, and heat and moisture exchanger filter. To date, there have been no COVID‐19 infections among the bronchoscopy team staff, whereas the overall Hospital staff COVID‐19 prevalence rate has exceeded 13.5% (667/4949). Conclusion: Emergency bronchoscopy procedures on COVID‐19 infected patients or patients with unknown infection status can be safely performed using modified full‐face snorkel masks.